Cardiovascular Health of Filipinos in the United States: A Review of the Literature. (September 2016) - Abesamis, Carol Jean; Fruh, Sharon; Hall, Heather; Lemley, Trey; Zlomke, Kimberly R.
Purpose: Filipino Americans (FAs) are at high risk for cardiovascular disease. The purpose of this literature review is to enhance understanding of cardiovascular health among FAs.Design: Databases searched: MEDLINE (via PubMed), Google Scholar, Journals@OVID, and EBSCO databases including CINAHL Complete. Health Source: Nursing/Academic Edition, Academic Search Complete, and Biological Abstracts 1969-Present. Key terms used: FAs and cardiovascular disease. Criteria for inclusion: peer-reviewed empirical articles published in English.Findings/Results: A total of 51 studies were identified and 27 were selected for the review based on relevance to nursing care for FAs. Three main themes emerged from the literature reviewed: risk factors and disease prevalence, health promotion, and health beliefs/practices.Discussion/Conclusions: The literature review identified that FAs were at high risk for cardiovascular disease, hypertension, type 2 diabetes, and metabolic syndrome at lower BMI levels.Implications for Practice: Health care providers should implement prevention strategies and interventions for the FA population to ensure the best outcomes.